Structural factors affecting the crystal-chemical variability in Al-rich K-dioctahedral 2M1 micas. (27th May 2019) - Zviagina, Bella B.; Drits, Victor A.
Abstract: To reveal the factors that determine the different ranges of compositional variations in high- and low-temperature Al-rich K-dioctahedral micas, relationships between structural parameters and cation composition were analysed for: (1) a series of synthetic 2 M 1 muscovite–phengite–aluminoceladonite samples; and (2) Al-rich, K-dioctahedral 2 M 1 micas with previously published refined structural data. The dependences of the unit-cell parameters on cation composition and the variations in tetrahedral and octahedral lateral dimensions and sheet thicknesses, interlayer distances and tetrahedral rotation angles were analysed and compared with those found previously for the series 1 M trans -vacant ( tv ) illite–1 M aluminoceladonite. The similarities in the variations of unit-cell parameters with cation composition observed in 2 M 1 and 1 M natural and synthetic K-dioctahedral micas imply that these variations are controlled by similar – albeit not identical – structural factors. A major structural factor is the readjustment of the differently sized tetrahedral and octahedral sheets, which is realized in a different manner in micas formed under different pressure and temperature conditions.